Spinco Model 119 Amino Acid Analyzer (1960)
First marketed in 1960, the Beckman/Spinco Model 120 Amino Acid Analyzer allowed users to quickly perform amino acid chromatography. This is a related, contemporary model.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Amino acids--Analysis; Beckman Instruments, Inc.